Revealing Novel Power Laws and Quantization in Electrospinning Considering Jet Splitting—Toward Predicting Fiber Diameter and Its Distribution Part II Experimental - Schubert, Dirk W.; Allen, Vincent; Dippel, Ursula (Advanced Engineering Materials, 2021)
Blends of poly‐ϵ‐caprolactone (PCL) with two different molar masses are deliberately varied to change viscosity independent of polymer concentration enabling to separate viscosity and a direct concentration dependence of the fiber diameter in the electrospinning process. Multiple distributions as a result of jet splitting are determined and analyzed. The existence of essentially two modes in fiber diameter frequency distribution, the base mode and the split mode, is revealed, whereas the scaling laws for each mode can be validated according to the latest theory. Finally, the theoretical predicted upper limit 22" role="presentation">2√2 of the ratio of standard deviation of fiber diameter and average fiber diameter is validated.
Keywords: distribution; electrospinning; fiber diameter; jet splitting; power laws